Blood group O is associated with ARDS development but exhibits lower mortality in the intensive care unit – A retrospective multicentre study - Hazem Koozi; Alma Dannäs; Patrik Johnsson; Attila Frigyesi (European Clinical Respiratory Journal)
Background Acute respiratory distress syndrome (ARDS) is a common cause of respiratory failure in the intensive care unit (ICU). Previous studies have suggested that blood group A increases the risk of developing ARDS following sepsis and major trauma. This study investigated the association between ABO and Rh blood groups and ARDS development and mortality in ARDS.Methods Patients admitted to the ICUs at Skåne University Hospital in Lund and Malmö, Sweden, in 2016 were retrospectively screened for ARDS according to the Berlin definition. Clinical data, patient characteristics, lab results, and survival data were collected from medical records and registry data. In addition, chest radiographs were reviewed by radiologists. ARDS development and 30-day mortality were analysed using multivariable logistic regression.Results A total of 1439 ICU patients were included. Of these, 10% had ARDS. Blood group O was associated with an increased risk of having or developing ARDS compared to blood group A (odds ratio [OR] 1.79, 95% confidence interval [CI] 1.13–2.84, p = 0.014). Among ARDS patients, blood group O had decreased 30-day mortality compared to blood group A (OR 0.25, 95% CI 0.09–0.67, p = 0.007). The Rh blood group was not associated with ARDS development or mortality.Conclusion In this study of ICU patients, blood group O was associated with an increased risk of having or developing ARDS but a decreased mortality in ARDS compared to blood group A. Further studies are needed to clarify the relationship and underlying mechanisms of the ABO blood group and ARDS.